Laptops and Fourth Grade Literacy: Assisting the Jump over the Fourth-Grade Slump - Suhr, Kurt A.; Hernandez, David A.; Grimes, Doug; Warschauer, Mark (The Journal of Technology, Learning and Assessment, 2010)
School districts throughout the country are considering how to best integrate technology into instruction. There has been a movement in many districts toward one-to-one laptop instruction, in which all students are provided a laptop computer, but there is concern that these programs may not yield sufficiently improved learning outcomes to justify their substantial cost. And while there has been a great deal of research on the use of laptops in schools, there is little quantitative research systematically investigating the impact of laptop use on test outcomes, and none among students at the fourth-to-fifth grade levels. This study investigated whether a one-to-one laptop program could help improve English language arts (ELA) test scores of upper elementary students, a group that often faces a slowdown of literacy development during the transition from learning to read to reading to learn known as the fourth-grade slump. We explore these questions by comparing changes in the ELA test scores of a group of students who entered a one-to-one laptop program in the fourth grade to a similar group of students in a traditional program in the same school district. After two years’ participation in the program, laptop students outperformed non-laptop students on changes in the ELA total score and in the three subtests that correspond most closely to frequent laptop use: writing strategies, literary response and analysis, and reading comprehension.